2019
DOI: 10.2460/javma.255.3.366
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of precursor-targeted immune-mediated anemia in dogs: 66 cases (2004–2013)

Abstract: OBJECTIVE To characterize the clinical features of dogs with precursor-targeted immune-mediated anemia (PIMA). ANIMALS 66 dogs with PIMA. PROCEDURES Electronic record databases of a teaching hospital were searched to identify dogs with a diagnosis of nonregenerative anemia between 2004 and 2013. Inclusion criteria included persistent nonregenerative anemia (Hct ≤ 30% and reticulocyte count < 76,000 reticulocytes/μL), cytologic findings supportive of ineffective bone marrow erythropoiesis, and absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
104
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(130 citation statements)
references
References 17 publications
7
104
3
Order By: Relevance
“…The diagnosis of immune‐mediated hemolytic anemia (IMHA) can be made confidently in dogs that fulfill the criteria outlined recently in the American College of Veterinary Internal Medicine (ACVIM) consensus statement 1 . Within 5 days of becoming anemic, dogs with IMHA typically develop erythroid regeneration 2 ; however, 30% to 55% remain nonregenerative with a corrected reticulocyte percentage (CR%) ≤1.0, which has been ascribed to destruction of erythroid progenitors by phagocytes in the bone marrow (BM) (rubriphagocytosis) 1,3‐7 . Similar rubriphagocytosis occurs also in dogs with nonregenerative anemia that lack evidence of peripheral immune‐mediated erythroid destruction or hemolysis, recently described as precursor‐targeted immune‐mediated anemia (PIMA) 3,8 .…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of immune‐mediated hemolytic anemia (IMHA) can be made confidently in dogs that fulfill the criteria outlined recently in the American College of Veterinary Internal Medicine (ACVIM) consensus statement 1 . Within 5 days of becoming anemic, dogs with IMHA typically develop erythroid regeneration 2 ; however, 30% to 55% remain nonregenerative with a corrected reticulocyte percentage (CR%) ≤1.0, which has been ascribed to destruction of erythroid progenitors by phagocytes in the bone marrow (BM) (rubriphagocytosis) 1,3‐7 . Similar rubriphagocytosis occurs also in dogs with nonregenerative anemia that lack evidence of peripheral immune‐mediated erythroid destruction or hemolysis, recently described as precursor‐targeted immune‐mediated anemia (PIMA) 3,8 .…”
Section: Introductionmentioning
confidence: 99%
“…On signalment, spayed females were significantly overrepresented in MDs. In previous studies, spayed females were also significantly predisposed to be diagnosed with NRIMA, PRCA, and PIMA [2,17,22], but the underlying causes have been unknown.…”
Section: Discussionmentioning
confidence: 96%
“…As a result, MD was identified as a predisposed breed of non-neoplastic bone marrow disorders in Japan. In the United States, Miniature Dachshunds were reported as a predisposed breeds for PIMA [2]. It was reported that MD was a breed commonly predisposed to inflammatory colorectal polyps and sterile panniculitis, which were rare in other breeds [16,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations